FDG-PET/CT versus bone marrow biopsy in bone marrow involvement in newly diagnosed paediatric lymphoma: a systematic review and meta-analysis - Zhizhuo Li; Chengxin Li; Bingrong Chen; Lijun Shi; Fuqiang Gao; Peixu Wang; Wei Sun (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Bone marrow infiltration (BMI) is a devastating stage of paediatric lymphoma. Prompt diagnosis of BMI in newly diagnosed paediatric lymphoma patients is critical but can be very challenging at present. Methods We systematically retrieved studies from PubMed, EMBASE, and the Cochrane Library. Data extraction and quality assessment were performed by two reviewers independently. A total of nine eligible studies were included in the quantitative analysis. Results The pooled sensitivity and specificity of FDG-PET/CT for diagnosing BMI in newly diagnosed paediatric lymphoma patients were 0.97 (95% confidence interval [CI], 0.93 to 0.99) and 0.99 (95% CI, 0.98 to 0.99), respectively. The pooled PLR, NLR, and DOR were 79.9 (95% CI, 42.7 to 149.6), 0.03 (95% CI, 0.01 to 0.17), and 2414.6 (95% CI, 989.6 to 5891.4), respectively. The AUC of FDG-PET/CT for BMI was 1.00 (95% CI, 0.99 to 1.00). Compared with FDG-PET/CT, BMB had a lower pooled sensitivity (0.44, 95% CI, 0.34 to 0.55) and comparable pooled specificity (1.00, 95% CI, 0.92 to 1.00). Conclusion Compared with BMB, FDG-PET/CT was a more valuable diagnostic method for evaluating BMI in paediatric Hodgkin and non-Hodgkin lymphoma patients with extremely high diagnostic accuracy.